A system dynamics model for optimal allocation of natural gas to various demand sectors. (2nd September 2019) - Daneshzand, Farzaneh; Amin-Naseri, Mohammad Reza; Asali, Mehdi; Elkamel, Ali; Fowler, Michael
Highlights: A natural gas supply and demand system is modeled using system dynamics. The optimal consumption share of each demand sector is determined through differential pricing. Environmental and economic objective functions are investigated. The residential sector has a much smaller share and export and transportation a much larger share of the recommended consumption mix in 2040. Appropriate policies will result in up to 11% reduction in CO2 emission on the demand side. Abstract: Natural gas is the most promising fossil fuel in the transition to a low-carbon energy future, and many countries have long term plans to increase its share in their energy supply mix through pricing regulations. While these policies encourage substitution of natural gas with more polluting fossil fuels, its over consumption and inefficient use can lead to misallocation of resources and CO2 emission increase. This paper develops a supply-demand model to optimally allocate natural gas to various demand sectors through determining a price path for each sector. The dynamic effects of price on demand, and income on supply are modeled using system dynamics. The model is applied to a case study on the optimal consumption share of each demand sector according to economic and environmental criteria. The results show that the residential sector should have a much smaller and export much larger share of the recommended consumption mix in 2040. Graphical abstract: Image, graphical abstract